STAGES OF ISLAMIZATION OF SCIENCE ACCORDING TO ISMAIL RAJI AL-FARUQI AS UNITY OF SCIENCES EFFORTS AND IMPLEMENTATION IN THE PRACTICAL GUIDANCE OF CHEMISTRY - Prastyo, Budiman (Unnes Science Education Journal, 2018)
This research explains the concept of Islamization from an influential figure of Islam, Ismail Raji Al-Faruqi. He was born in Jaffa, Palestine at 1st January 1921. He was born in the middle of conflict between the countries to Israel. An influencer to Islamic nuance of science, he was one of the figures in the raising movement of Islamic at the First World Conference on Muslim Education in 1977 in Mecca. The path of the movement (1970s) contributes to the concept of Islamization. It is claimed that his mindset is also influenced by the activist of Islamization, Syed Muhammad Naquib Al-Attas. The paradigm of this research is qualitative paradigm. The primary data were obtained from Ismail Raji Al-Faruqi’s book entitled Islamization of Knowledge: General Principles and Work Plan. Meanwhile, the secondary source came from journals, books, archives, or related documentation. Thus, the data were collected by library research by using some related literatures. The method of primary data interpretation used textual, contextual, and contextualized interpretation (hermeneutics effort). The writer also reviewed some sources constructed as systematic thoughts and implement it to the planning strategy of chemistry’s practicum. This research aimed to explore ideas of Ismail Raji Al-Faruqi regading the paradigm of Unity of Sciences. This theoretical framework was then developed to plan chemistry’s practicum for Senior High School students.